SEGMENTATION OF VESSELS IMAGES ON ANGIOGRAMS IN SPACE OF TRANSFORMATION COEFFICIENTS WITH COMMON WAVELET FUNCTIONS - Polyakova, Marina (International Journal of Computing, 2011)
The method of vessel segmentation on angiogram is elaborated. It includes the analysis of own values of Hessian for every pixel of image. The elements of Hessian calculated from the image convolution by the common wavelet functions with a compact support. This decreases the conputational complexity of method of segmentation of angiograms due to replacement of a few levels of data processing by one.